2016
DOI: 10.1063/1.4964596
|View full text |Cite
|
Sign up to set email alerts
|

Development of the method for the electron beam spatial distribution determination in the transverse plane

Abstract: Abstract.The article presents the device destined for flux density distribution of electrons in the beam cross section without consumables, with a resolution of about 1 mm and slightly dependent on the electron energy. The possibility of the cross section reconstruction of the electron flux density distribution by the inverse Radon transformation is shown. The results of mathematical reconstruction are illustrated and upon which the projections optimum quantity are specified. In the paper the experimental set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Previous studies [27,28] have also shown that an angular step of Δ𝜑 = 10 • is optimal as it ensures the reliability of the results obtained with a minimal data collection time. Therefore, for all experiments, a 10 • angle step was chosen.…”
Section: Experimental Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [27,28] have also shown that an angular step of Δ𝜑 = 10 • is optimal as it ensures the reliability of the results obtained with a minimal data collection time. Therefore, for all experiments, a 10 • angle step was chosen.…”
Section: Experimental Schemementioning
confidence: 99%
“…After formation, the deformed beam was sent to the developed detecting system. A deformed beam with a complex shape was considered in this study because of previous studies [27,28] had reported the possibility to measure the profile of a beam shaped close to a circle even with the presence of a lot of noise.…”
Section: Experimental Schemementioning
confidence: 99%
“…In our previous work [11], we proposed a method to determine the spatial distribution of the electron beam in the transverse plane. However, the induction effect arises during the scanning of the electron beam by a thin metal plate.…”
Section: Introductionmentioning
confidence: 99%